Coping strategies and the Salutogenic Model in future oral health professionals. Issue 1 (December 2016) - Gambetta-Tessini, Karla; Mariño, Rodrigo; Morgan, Mike; Anderson, Vivienne
Abstract Background Attention to the role of context in shaping individuals' coping strategies is necessary. This study used the Salutogenic Model (SM) as a framework to identify the coping strategies of oral health profession students from three countries. Methods Students from Australia, New Zealand and Chile were invited to participate in this cross-sectional study, and were given a questionnaire including socio-demographics, the Perceived Stress Scale, The SOC-13 and the Brief COPE. Descriptive analysis, correlation analysis and profile analysis were computed using SPSS v 20.0. Results Eight-hundred and ninety-seven valid questionnaires were returned, achieving a 44 % response rate. The coping dimension that the participants most commonly reported using was "Active Coping" with a mean value of 5.9 ± 1.5. Chilean respondents reported higher stress levels (19.8 vs. 17.7) and a lower Sense of Coherence (55.6 vs. 58.0) compared to Australian/New Zealand participants (p  < 0.001). The SOC was positively correlated with active coping (p  < 0.01) and positive reframing (p  < 0.01). Profile analysis showed that when the differences in responses by sex were accounted for, there was no significant effect by country on the coping strategies used (p  < 0.32). Conclusion This initial investigation provides insights into the students' coping strategies and the validity of the SM. Students reporting high SOC scores where those who demonstrated the use of active coping and positive reframing as strategies to deal with stressful situations, which indicates the accuracy of the theoretical framework of the SM in health education environments. The results also suggest that a distinctive coping strategy pattern may apply to all participants, regardless of their country and sex.